Digitalisation of firms and (type of) employment - Sousso Bignandi; Cédric Duprez; Céline Piton (National Bank of Belgium, 2024)
This paper investigates the effects of digitalisation on firm-level employment and workforce composition in Belgium from 2003 to 2019, using a novel dataset that merges ICT expense data with administrative employment records. We find that digitalised firms experienced higher employment growth relative to non-digitalised firms, driven by both increased hiring and higher retention rates. The effect is particularly pronounced in large firms and reflects both faster employment growth in expanding firms and slower declines in shrinking firms. Digitalisation also significantly altered workforce composition, leading to a decrease in the share of low-educated workers and an increase in the share of highly educated workers, alongside shifts in the age distribution towards middle-aged workers. Our analysis employs a long-difference regression approach, well suited to capturing the gradual nature of ICT investments. While endogeneity concerns prevent causal interpretation, we show robust correlations between digitalisation and employment growth. The study contributes to the literature by providing a granular measure of digitalisation at firm level, offering new insights into the dynamics of worker turnover and sectoral differences, and by shedding light on the heterogeneous impact of digitalisation across worker education levels and age groups.
Keywords: D22; D25; J21; J24; 330; Digitalisation; employment; firms